THE INFLUENCE OF COOPERATIVE LEARNING MODEL TYPE NHT (NUMBERED HEADS TOGETHER) To THE LEARNING OUTCOMES OF STUDENTS ON THE MATERIAL BATTERY WORK PRINCIPLE AND CONSTRUCTION OF BATTERIES IN CLASS X SMK KARSA MULYA PALANGKA RAYA IN ACADEMIC YEAR 2016/2017 - Ricky Santoso (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2018)
The one of obstacles faced by students in understanding the material Battery Work Principle and Construction of Batteries with Conventional learning models can be seen from the learning outcomes of students who reach the level of mastery learning by 52%. Learning outcomes of students does not reach KKM which is passing grade at 70 for school standard score. This study aims to determine the influence of the learning model NHT which is opposite to the learning outcomes of students on the course subject of Battery Work Principle and Construction of Batteries in class X of SMK Karsa Mulya Palangka Raya on academic Year 2016/2017. The method used is the pre-test and post-test control group design. The population of this research is class X of Light Vehicle Engineering and Motorcycle Engineering A. This research took a sample of the class by Simple Random Sampling and the obtained the results of class X mechanical Light Vehicle A as a class experiment with the number of 34 Students, and the class X of mechanical Light Vehicle B as the Control class with the number of 35 students. Data collection has conducted using the test, which consisting of pre-test and post-test. The Data was collected then analyzed statistically by using the average pre-test, post-test and difference of two averages. Based on the results of the analysis of the data pre-test the average value of the experimental class (42.65) and control class (48.34). This can be categorized as substandard due to have not reached the KKM. Data on posttest of average values are the experimental class (80.98) and control class (72.28), in which it means that the class has reached the KKM with the degree of difference is quite far between before the Treatment and after given Treatment. From the results of the analysis has showed that the learning outcomes of students of class X SMK Karsa Mulya Palangka Raya has performed the normal distribution. Based on results obtained by statistical analysis, the conclusion is that there is Influence of Learning Model NHT (Numbered Heads Together) on the material Battery Work Principle and Construction of Batteries of the class X TKR SMK Karsa Mulya Palangka Raya”. Based on the results of the study it shows that the influence of the results of student learning outcomes occurring in class experiments with the learning model NHT is well-performed than the control class with the conventional learning models on the material Battery Work Principle and Construction of Battery.